Pensar e mandar fazer ciência. A criação da Junta de Educação Nacional e a política de organização científica do Estado Novo - Maria Fernanda Rollo; Maria Inês Queiroz; Tiago Brandão (Ler História, 2011)
In the early twentieth century, in a context of growing recognition and appreciation of science, was born the idea of creating an independent agency designed to promote and organize scientific funding in Portugal. The Junta Nacional de Educação (JEN), created in 1929, was the first Portuguese institution whose mission was to promote and support science development and organization. This article traces the genesis of JEN, analyzing the principles and assumptions that were at its origin. It contextualizes and describes the activity of the JEN in the relations between science and Estado Novo.